Influence of UV-B on expression profiles of genes involved in the development of autophagy by means of microtubules - Olenieva, V.D.; Lytvyn, D.I.; Yemets, A.I.; Blume, Ya.B. (Reports of the National Academy of Sciences of Ukraine, 2018)
Transcriptome analysis of key genes involved in realization of autophagy induced by UV-B irradiation in Arabidopsis thaliana cells is conducted. Changes in expression of α-tubulin and atg8 genes had clearly defined doseand time-dependent nature. Overexpression of tub4 and atg8a shown at time points of 3 and 24 h after irradiation indirectly testifies to the interaction between the structural units of autophagosomes and microtubules. Expression profiles of elp3/deacetylases, as well as hexokinases, denote the crucial role of α-tubulin acetylation for autophagic response - a stage preceding the development of programmed cell death.